2016
DOI: 10.3168/jds.2015-10042
|View full text |Cite
|
Sign up to set email alerts
|

Conjugated linoleic acids influence fatty acid metabolism in ovine ruminal epithelial cells

Abstract: Conjugated linoleic acids (CLA), particularly cis-9,trans-11 (c9t11) and trans-10,cis-12 (t10c12), are used as feed additives to adapt to constantly increasing demands on the performance of lactating cows. Under these feeding conditions, the rumen wall, and the rumen epithelial cells (REC) in particular, are directly exposed to high amounts of CLA. This study determined the effect of CLA on the fatty acid (FA) metabolism of REC and expression of genes known to be modulated by FA. Cultured REC were incubated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 65 publications
(78 reference statements)
0
2
0
Order By: Relevance
“…Due to the continuous production of CLA during the ruminal microbial biohydrogenation process, ruminal epithelial cells are directly exposed to a certain amount of CLA (Masur et al, 2016), and the positive immunoregulatory effect of CLA on gastrointestinal barrier health has been extensively verified in both animal and human studies (Chen et al, 2019;Coelho et al, 2019). Considering that the rumen immune system must continuously face challenges from antigens of lysed dead microbial cells or LPS from the shedding gram-negative bacteria within the rumen, we hypothesized that CLA may contribute to the immune response of the ruminal epithelium.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the continuous production of CLA during the ruminal microbial biohydrogenation process, ruminal epithelial cells are directly exposed to a certain amount of CLA (Masur et al, 2016), and the positive immunoregulatory effect of CLA on gastrointestinal barrier health has been extensively verified in both animal and human studies (Chen et al, 2019;Coelho et al, 2019). Considering that the rumen immune system must continuously face challenges from antigens of lysed dead microbial cells or LPS from the shedding gram-negative bacteria within the rumen, we hypothesized that CLA may contribute to the immune response of the ruminal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…Among the broad range of CLA isomers, cis-9, trans-11 CLA and trans-10, cis-12-CLA have been the most studied bioactive isomers (Bruen et al, 2017), and many healthy characteristics have been associated with the results of interactions between these two major isomers, such as anti-obesogenic, anti-carcinogenic, anti-inflammatory and immune enhancement properties (Kim et al, 2016;Viladomiu et al, 2016;Garibay-Nieto et al, 2017). Previous studies on ruminants found that the addition of cis-9, trans-11 CLA and trans-10, cis-12 CLA can modify the fatty acid profile of sheep's milk and beef (Schiavon et al, 2011;Pellattiero et al, 2015), affect the fatty acid metabolism pathways in ovine ruminal epithelial cells (Masur et al, 2016) and lower the milk fat content and improve the energy balance in dairy cows during early lactation (Qin et al, 2018). Basiricò et al (2017) also found that supplementation of cis-9, trans-11 CLA and trans-10, cis-12 CLA protected bovine mammary epithelial cells against H 2 O 2 -induced oxidative damage.…”
Section: Introductionmentioning
confidence: 99%